Systematic evaluation of bromine‐free flame‐retardant systems in acrylonitrile‐butadiene‐styrene. Issue 13 (9th November 2021) - Bachinger, Angelika; Sandinge, Anna; Lindqvist, Karin M.; Strid, Anna; Gong, Guan
Abstract: A systematic investigation of phosphorus‐based flame‐retardant (PFR) systems in acrylonitrile‐butadiene‐styrene (ABS) is presented. The effect of various PFRs, combinations thereof and influence of different synergists is studied in terms of fire and mechanical performance, as well as toxicity of resulting ABS. Sustainable flame‐retardant systems with a promising effect on the fire‐retardant properties of ABS are identified: A combination of aluminum diethylphosphinate and ammonium polyphosphate is shown to exhibit superior flame‐retardant properties in ABS compared to other studied PFRs and PFR combinations. Among a variety of studied potential synergists for this system, a grade of expandable graphite with a high‐initiation temperature and a molybdenum‐based smoke suppressant show the most promising effect, leading to a significant reduction of the peak heat release rate as well as the smoke production rate. Compared to current state‐of‐the‐art brominated flame‐retardant for ABS, the identified flame‐retardant systems reduce the maximum smoke production rate by 70% and the peak heat release rate by 40%. However, a significant reduction of the impact performance of the resulting ABS is identified, which requires further investigation. Abstract : A systematic comparison of various phosphorus‐based flame‐retardant systems in ABS regarding fire and mechanical performance and toxicity is presented. Promising sustainable flame‐retardant systems for ABS are identified, reducing smoke production and peak heat release rate compared to brominated flame‐retardants. Reduction of the impact strength indicates that investigations on the morphology of the studied systems are required for further optimization.